Kultura popularna i tożsamość – obraz Śląska w tekstach polskiego rapu - Stępień, Patryk (Studia Edukacyjne, 2024)
Rap is one of the most popular music types in Poland. The content of the songs includes various descriptions of social life, the world of values, and cultural patterns presented from the perspective of the artists, who in their works usually describe what they experience. These bottom-up narratives become a source of inspiration for listeners, especially young people. This article contains content analysis results of rap lyrics and music videos concerning regional aspects in the Silesia district. The identified contexts and worldview elements can provide a basis for educators’ discussions with young people. Attempting to understand issues important to young people raised in works of popular culture can be an element of understanding them and seeing factors that may be important in identity formation, including regional identity.